Symptomatic and essential palatal tremor. 3. Abnormal motor learning. Issue 5 (May 1996) - Deuschl, G; Toro, C; Valls-Solé, J; Hallett, M
Abstract : BACKGROUND--Palatal tremor is divided into symptomatic palatal tremor (SPT) and essential palatal tremor (EPT) on the basis of clinical features. The inferior olive seems to be abnormal in SPT, but not EPT. Because the inferior olive is likely to be involved in several types of motor learning, it is hypothesised that motor learning would be abnormal in patients with SPT, but not those with EPT. METHODS--In six patients with SPT and four patients with EPT, two motor learning paradigms were studied--the classical conditioning of an acoustically elicited eyeblink with electrical supraorbital nerve shock and a test of adaptation of ballistic arm movements to a change of the gain. RESULTS--Classical conditioning was impaired unilaterally or bilaterally in the patients with SPT, depending on whether they had unilateral or bilateral abnormalities of the inferior olives, except for the two least affected patients. All but one of the patients with EPT had normal conditioning. On the adaptation test of arm movements, most of the patients with SPT had impaired learning of the arm contralateral to the hypertrophied inferior olive, regardless of whether the abnormality was unilateral or bilateral, but all patients with EPT had normal results. CONCLUSIONS--In SPT pseudohypertrophy of the inferior olive leads to defective cerebellar function, whereas in EPT the inferior olive functions normally.